2016
DOI: 10.1016/j.measurement.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of tracking laparoscopic instruments in a box trainer using a Leap Motion Controller

Abstract: Motion analysis is employed to assess minimally invasive surgical psychomotor skills in box trainers. Tracking of laparoscopic instruments requires sensor-based systems that can be expensive, limit movements and modify their ergonomic properties. We evaluate the feasibility of using Leap Motion as a cheap, unobtrusive alternative. Four experiments were performed to determine its precision while tracking a laparoscopic instrument inside and outside a box trainer. Static long and short term precision of the Leap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…This arrangement was the result of a process of trial and error, which showed that setting the LMC at this angle with respect to the horizontal plane ostensibly improved the detection of the forceps. Another significant change during the design was that the original black color of the shaft of the forceps did not facilitate reading by the LMC [ 45 ]; therefore, they were painted white in the final prototype ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…This arrangement was the result of a process of trial and error, which showed that setting the LMC at this angle with respect to the horizontal plane ostensibly improved the detection of the forceps. Another significant change during the design was that the original black color of the shaft of the forceps did not facilitate reading by the LMC [ 45 ]; therefore, they were painted white in the final prototype ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…LMC has been analysed in a wide spectrum of applications including virtual grasping [11], where the absolute accuracy of the tracked hand is not of the main concern. The sensor has been evaluated for training laparoscopic surgeries as well [12]. LMC has been used in the past in robotic arm control applications [13,14], where the data from the sensor was processed on a computer and then transmitted to the robot controller.…”
Section: State Of Artmentioning
confidence: 99%
“…[99 ] To study the possibility of tracking laparoscopic instruments using the LMC in a box trainer Experiment .…”
Section: User Testingmentioning
confidence: 99%
“…In 2014, the method was shown to represent a further step forward in the development of advanced training systems in MIS using the MicronTrackTM (Claron Technology Inc., Toronto, Canada) [54]. Beginning in 2016, several authors proposed the interesting possibility of using COTS devices for tracking of laparoscopic instruments, both the LMC [56,95,98,99] and the MK [100]. Others used the approach of tracking hand movements during MIS training [55,96].…”
Section: Interventionsmentioning
confidence: 99%